Lenvatinib for the treatment of renal cell carcinoma. (4th May 2018) - Roviello, Giandomenico; Corona, Silvia Paola; Bozza, Giovanni; Aieta, Michele; Generali, Daniele; Rodriquenz, Maria Grazia; Mileo, Anna Maria; Imperatori, Marco; Ianza, Anna; Conca, Raffaele; Sobhani, Navid
ABSTRACT: Introduction : Renal cell carcinoma (RCC) accounts for 2–3% of all solid tumors. Expression of the receptor for the vascular endothelial growth factor (VEGF) is one of the most common features of RCC. Areas covered : Lenvatinib is a novel multi-kinase inhibitor that has been studied in several solid tumors. It has shown promising results in the treatment of RCC, especially when combined with everolimus, In this review, we summarize the available data of lenvatinib for the treatment of advanced/metastatic renal cell carcinoma. Expert opinion : Lenvatinib in combination with everolimus has provided encouraging results in both clinical and laboratory investigations showing that blocking angiogenesis and the mTOR signalling pathway could be a remarkable approach for treating RCC. As an additive to this type of approach it would be interesting in future clinical settings testing also the combination of lenvatinib and everolimus with immune-therapy.